Small-Firm Networks: Hybrid Arrangement or Organizational Form - Verschoore, Jorge Renato; Balestrin, Alsones; Perucia, Alexandre Souza (Organizações & Sociedade, 2014)
In the field of organizations, one relevant question is whether or not to consider networks as organizational forms. On the one hand, Williamson (1985) says that networks are hybrid arrangements. On the other, authors like Powell (1990) argue that networks constitute themselves as organizational forms. Given this dilemma, the present article proposes the analysis of organizational characteristics of small-firm networks (SFN). To reach such objective, twelve SFNs in distinct stages of development were analyzed. The results show that SFNs constitute themselves as singular organization forms which boundaries and identities are delineated by strategy, structure, coordination, processes and relationships.